THE IMPLEMENTATION OF CONTEXTUALIZATION IN TEACHING VOCABULARY TO ELEMENTARY STUDENTS : REACT: Relating, Experiencing, Applying, Cooperating, and Transferring: A Quasi-Experimental Study of the Fifth Grade Students in one of Elemntary Schools in Bandung - Rohayati, Tuti (2013)
ABSTRACT The aim of this study was to investigate the effectiveness of contextualization using REACT (Relating, Experiencing, Applying, Cooperating, and Transferring). This study adopted a quasi experimental design with pre-test and post-test non equivalent groups design, both experimental and control group. Homogeneity test was calculated in attempt to ensure that the variance of both groups is equal. Pre-test and post-test were administered to both experimental group and control group. The data analysis was calculated statistically by using SPSS 16.0. The result of this study revealed that REACT was significantly effective in improving students' vocabulary achievement. It can be seen from the statistical computation result of post-test score of experimental group (M=78.66) that was higher than control group (M=67.33). Key words: Contextualization, REACT, Vocabulary.